A study to observe the effects of infusion of 6% Hydroxyethyl starch (130/0.4) on renal function in cardiac surgical patients - Pradeep Kumar Das; Bhyravajosula Koumudi; Danda Vijaya Kumar; Rajeswara Rao S (Asian Journal of Medical Sciences, 2022)
Background: The possibility of nephrotoxic effect caused by hydroxy ethyl starch (HES) used as volume therapy in this particular setting is of major clinical concern. We conducted this retrospective study to look for the possible nephrotoxic effects and other systemic adverse effects if any, of 6% HES 130 kD, 0.4 DS used as intraoperative volume expander in the cardiac surgery setting. Aims and Objectives: This study aims to determine whether the infusion of 6% hydroxyethyl starch (130/0.4) harms renal function in cardiac surgical patients. Materials and Methods: The present study was a retrospective study. Sixty-six patients who received crystalloids with hydroxyethyl starch and a matched control of 66 patients based on age and sex and other baseline parameters who received crystalloids only were part of the study. The data extracted from the electronic medical record include patient demographics, details for additive EURO score, and pre-operative data that include details of comorbid illnesses, namely, hypertension and diabetes, plasma hemoglobin, serum creatinine, and eGFR. Results: There is no statistically significant difference in serum creatinine and incidence of post-operative renal dysfunction between the study groups. There was a higher rate of re-exploration and duration of intensive care unit, and hospital stay. Conclusion: In our study, HES 130/0.4 in the dose used as a plasma expander did not adversely affect renal function in cardiac surgical patients undergoing CABG. The study recommends further detailed studies in this area involving multiple centers.